2022
DOI: 10.1002/art.42023
|View full text |Cite
|
Sign up to set email alerts
|

Urine Proteomics and Renal Single‐Cell Transcriptomics Implicate Interleukin‐16 in Lupus Nephritis

Abstract: Objective Current lupus nephritis (LN) treatments are effective in only 30% of patients, emphasizing the need for novel therapeutic strategies. We undertook this study to develop mechanistic hypotheses and explore novel biomarkers by analyzing the longitudinal urinary proteomic profiles in LN patients undergoing treatment. Methods We quantified 1,000 urinary proteins in 30 patients with LN at the time of the diagnostic renal biopsy and after 3, 6, and 12 months. The proteins and molecular pathways detected in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
47
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 51 publications
6
47
1
Order By: Relevance
“…Our findings thus suggest that the discriminatory potential of dt-u-IL-16 for PLN should be further investigated and validated. Our findings extend recent data reported by Fava et al , 10 who identified u-IL-16 as a marker of histological activity in PLN.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings thus suggest that the discriminatory potential of dt-u-IL-16 for PLN should be further investigated and validated. Our findings extend recent data reported by Fava et al , 10 who identified u-IL-16 as a marker of histological activity in PLN.…”
Section: Discussionsupporting
confidence: 93%
“…This goes in line with findings by Fava et al, where no correlation with proteinuria was found. 10 We found that more than half of the kidney infiltrating cells in LN express IL-16 protein. Numerically higher numbers of IL-16 positive cells were observed in patients without ongoing treatment.…”
Section: Lupus Nephritismentioning
confidence: 72%
“…With respect to renal response, longitudinal reduction in urinary CD163 abundance was strongly associated with complete response (per the definition used in the Methods) in the BLISS-LN trial regardless of treatment arm. Urinary CD163 is a macrophage marker which correlates with histological activity index on renal biopsy and has been previously associated with renal response to LN therapy in at least two independent studies, namely our prior findings in the Accelerating Medicines Partnership in Rheumatoid Arthritis/SLE 4 and also those of Mejia-Vilet et al . 2 As shown in figure 1 , reduction in activated leucocyte cell adhesion molecule (ALCAM) and interferon beta (IFNb) were also seen in renal responders versus non-responders.…”
Section: Discussionmentioning
confidence: 78%
“…CKD progression in patients with proteinuric response may be secondary to persistent intrarenal inflammation,8 9 profibrotic processes18 or other mechanisms not yet discovered. We speculate that specific urinary proteins that correlate with intrarenal inflammation or active fibrosis–rather than the total amount of protein in the urine–could potentially be superior predictors of the development of CKD in LN 19 20. Urine proteomic biomarkers of intrarenal matrix remodelling and inflammation can successfully detect early CKD in various other nephropathies and predict risk of CKD progression in diabetic nephropathy 21–23.…”
Section: Discussionmentioning
confidence: 99%